Intrusion of saline water into a coastal aquifer containing palaeogroundwater in the Viimsi peninsula in Estonia - Raidla, Valle; Pärn, Joonas; Aeschbach, Werner; Weißbach, Therese (Geosciences, 2019)
The Viimsi peninsula is located north-east of Tallinn, capital of Estonia. The Cambrian-Vendian (Cm-V) aquifer system is a sole source of drinking water in the area. Historically, the groundwater exploitation has led to freshening of groundwater in the peninsula, but in recent years an increase in chloride concentrations and enrichment in δ18O values has been detected, but in recent years hydrochemical parameters indicate an increasing influence of a saline water source. The exact origin of this saline water has remained unclear. The aim of the current study is to elucidate whether the increase in Cl− concentrations is related to seawater intrusion or to the infiltration of saline water from the underlying crystalline basement. To identify the source of salinity, chemical composition of the groundwater and the isotope tracers (e.g., δ18O and radium isotopes) were studied in the Viimsi peninsula in the period from 1987 to 2018. Our results show that chemical composition of Cm-V groundwater in the peninsula is clearly controlled by three-component mixing between glacial palaeogroundwater, saline water from the underling crystalline basement and modern meteoric water. The concentrations of Ra are also significantly affected by the mixing, but the spatial variation of radium isotopes (226Ra and 228Ra) suggests the widespread occurrence of the U in the surrounding sedimentary sequence. Our hypothesis is that, in addition to U originating from the crystalline basement, some U could be associated with secondary U deposits in sedimentary rocks. The formation of these secondary U deposits could be related to glacial meltwater intrusion in the Pleistocene. Although the results suggest that the infiltration of saline groundwater from the underlying crystalline basement as the main source of salinity in the study area, the risk of seawater intrusion in the future cannot be ruled out. It needs to be highlighted that the present groundwater monitoring networks may not be precise enough to detect the potential seawater intrusion and subsequent changes in water quality of the Cm-V aquifer system in the Viimsi peninsula.
Gesehen am 12.03.2019